INTEGRATING DIFFERENTIATED INSTRUCTION AND ARTIFICIAL INTELLIGENCE IN DEVELOPING STUDENTS’ ENGLISH READING AND WRITING SKILLS (Universal International Scientific Journal, 2026)
This thesis examines the integration of differentiated instruction with artificialintelligence (AI) and digital technologies in developing university students’ reading and writing skillsin English. Differentiated instruction addresses learners’ individual needs, proficiency levels, andlearning styles, enabling more inclusive and effective language instruction. The study emphasizes thattechnological integration alone is insufficient without a strong pedagogical foundation. Therefore,motivational, identity-based, and learner-centered approaches are incorporated to enhance students’engagement and investment in language learning. AI-supported digital tools provide personalizedfeedback, adaptive learning pathways, and opportunities for autonomous practice. The findingssuggest that combining differentiated instruction with AI and motivational pedagogical approachessignificantly improves students’ academic performance, self-confidence, and active participation inEnglish reading and writing tasks.
Keywords: differentiated instruction; artificial intelligence in education; digital learning